A Novel Fold‐Based Design Approach toward Printable Soft Robotics Using Flexible 3D Printing Materials. Issue 2 (4th December 2017) - Keong, Benjamin Ang Wee; Hua, Raye Yeow Chen
Abstract: Soft robotic technologies have been known to have various advantages over their rigid counterparts due to their compliant and deformable properties. They can carry out delicate object manipulation and perform complex maneuvers in confined spaces, which traditional robotics has difficulty with. The most widely adopted fabrication method for traditional soft elastomeric fluidic actuators is mold‐casting, which is cumbersome and involves several manual steps. Therefore, a substantial variability in performance and quality of these actuators arises directly from the manufacturing process. This paper presents on a novel fold‐based design of a 3D‐printed soft pneumatic bending actuator. In contrast to other works that rely on high‐end multimaterial 3D printers, a consumer‐grade open source 3D printer to fabricate soft pneumatic actuators in a fast and cheap way using fused deposition modeling technology has been adapted. This allows for consistency in both the quality of the actuators and their mechanical performance. The key findings in (1) a 3D‐printed fold‐based actuator fabrication process, (2) actuator characterization, and (3) a design‐centric approach toward different bending profiles for different applications are presented. Abstract : Manufacturing of soft pneumatic actuators could not have been easier with 3D printing of flexible materials. A novel fold‐based design‐based approach through 3D printing enhances the performance of soft pneumatic actuators while conferring abilities to bend into different configurations. This design can also be fundamentally used to manufacture soft pneumatic actuators found in a variety of functional applications.